Myc and ChREBP transcription factors cooperatively regulate normal and neoplastic hepatocyte proliferation in mice - Wang, Huabo (J Biol Chem, 2018)
Analogous to the c-Myc (Myc)/Max family of bHLH-ZIP transcription factors, there exists a parallel regulatory network of structurally and functionally related proteins with Myc-like functions. Two related Myc-like paralogs, termed MondoA and MondoB/carbohydrate response element–binding protein (ChREBP), up-regulate gene expression in heterodimeric association with the bHLH-ZIP Max-like factor Mlx. Myc is necessary to support liver cancer growth, but not for normal hepatocyte proliferation. Here, we investigated ChREBP's role in these processes and its relationship to Myc. Unlike Myc loss, ChREBP loss conferred a proliferative disadvantage to normal murine hepatocytes, as did the combined loss of ChREBP and Myc. Moreover, hepatoblastomas (HBs) originating in myc(−/−), chrebp(−/−), or myc(−/−)/chrebp(−/−) backgrounds grew significantly more slowly. Metabolic studies on livers and HBs in all three genetic backgrounds revealed marked differences in oxidative phosphorylation, fatty acid β-oxidation (FAO), and pyruvate dehydrogenase activity. RNA-Seq of livers and HBs suggested seven distinct mechanisms of Myc–ChREBP target gene regulation. Gene ontology analysis indicated that many transcripts deregulated in the chrebp(−/−) background encode enzymes functioning in glycolysis, the TCA cycle, and β- and ω-FAO, whereas those dysregulated in the myc(−/−) background encode enzymes functioning in glycolysis, glutaminolysis, and sterol biosynthesis. In the myc(−/−)/chrebp(−/−) background, additional deregulated transcripts included those involved in peroxisomal β- and α-FAO. Finally, we observed that Myc and ChREBP cooperatively up-regulated virtually all ribosomal protein genes. Our findings define the individual and cooperative proliferative, metabolic, and transcriptional roles for the “Extended Myc Network” under both normal and neoplastic conditions.